Implementasi Model PQ4R (Preview, Question Read, Reflect, Recite, dan Review) untuk Meningkatkan Hasil Belajar Siswa Kelas 4 SD Negeri 3 Tanggungharjo, Ngaringan - Eri Sumarti (Action Research Journal, 2022)
Indonesian language lessons essentially teach students to be able to communicate using correct and communicative sentences. Indonesian language lessons at school aim to improve the ability to communicate both orally and in writing. Based on this description, the aim of this research is to implement the PQ4R Model (Preview, Question Read, Reflect, Recite and Review) to improve the learning outcomes of Grade 4 Students at SD Negeri 3 Tulisharjo, Ngaringan in cycle I and cycle II. This research method is classroom action research which uses 2 cycles. The results of this research are that the implementation of the PQ4R Model (Preview, Question Read, Reflect, Recite, and Review) can improve the Learning Outcomes of Class 4 Students at SD Negeri 3 Tulisharjo. This is indicated by the increase in classical learning completeness in the research class, namely in the first cycle only 10 students reached the KKM out of a total of 16 students, increasing to 14 students who reached the KKM set by the school.